Liquid Metal Patterning and Unique Properties for Next‐Generation Soft Electronics. Issue 6 (15th January 2023) - Kim, Minwoo; Lim, Hyungjun; Ko, Seung Hwan
Abstract: Room‐temperature liquid metal (LM)‐based electronics is expected to bring advancements in future soft electronics owing to its conductivity, conformability, stretchability, and biocompatibility. However, various difficulties arise when patterning LM because of its rheological features such as fluidity and surface tension. Numerous attempts are made to overcome these difficulties, resulting in various LM‐patterning methods. An appropriate choice of patterning method based on comprehensive understanding is necessary to fully utilize the unique properties. Therefore, the authors aim to provide thorough knowledge about patterning methods and unique properties for LM‐based future soft electronics. First, essential considerations for LM‐patterning are investigated. Then, LM‐patterning methods—serial‐patterning, parallel‐patterning, intermetallic bond‐assisted patterning, and molding/microfluidic injection—are categorized and investigated. Finally, perspectives on LM‐based soft electronics with unique properties are provided. They include outstanding features of LM such as conformability, biocompatibility, permeability, restorability, and recyclability. Also, they include perspectives on future LM‐based soft electronics in various areas such as radio frequency electronics, soft robots, and heterogeneous catalyst. LM‐based soft devices are expected to permeate the daily lives if patterning methods and the aforementioned features are analyzed and utilized. Abstract : Room‐temperature liquid metal (LM)‐based electronics will bring advancements in soft electronics owing to its unique properties. However, patterning LM is difficult because of its rheological features. This resulted in various LM‐patterning methods. A choice of patterning method with understanding is necessary to utilize the properties of LM. Therefore, knowledge about patterning methods and properties for LM‐based soft electronics is provided.